Improved performance millimetre‐wave antenna array by using artificial materials. Issue 11 (29th July 2019) - Erfani, Elham; Tatu, Serioja
Abstract : A millimetre‐wave (MMW) 4 × 2‐element antenna array integrated with a soft surface structure is presented. The proposed antenna is alternatively interpreted as an array of overlapped eared‐aperture‐coupled‐patch‐antenna, fed by strip‐line feed‐network through a low loss and wideband strip‐line‐to‐grounded‐coplanar‐waveguide transition. It is shown that, compared to a 4 × 4‐element conventional planar array with a given aperture size, eight radiating elements are required to achieve an almost same directivity/gain by utilising the soft surface structure between elements of the array. By reducing the number of excited elements with this method, the feed‐network is simplified. Furthermore, being more noticeable in the E‐plane, where soft surface structure is used, the side lobe level is improved in both E‐ and H‐planes. Enhancements of matching and directivity/gain bandwidths are other advantages achieved with the proposed approach. In addition, it is feasible to use the proposed soft‐surface structure in developing larger antenna array packages that can be integrated with other parts of a radio frequency circuitry by using MMW interconnection technologies.